Wind energy facilities affect resource selection of capercaillie Tetrao urogallus. Issue 1 (25th January 2021) - Taubmann, Julia; Kämmerle, Jim‐Lino; Andrén, Henrik; Braunisch, Veronika; Storch, Ilse; Fiedler, Wolfgang; Suchant, Rudi; Coppes, Joy
Abstract : The recent increase in wind energy facilities (WEF) has led to concerns about their effect on wildlife. While the focus of most studies has mainly been on increased mortality of birds and bats due to collision, indirect effects, such as behavioural responses, are currently gaining attention. Indeed, effects of WEF on the behaviour of forest dwelling wildlife still remain largely unknown. Using GPS‐tracking of 16 individuals, we studied how seasonal resource selection of the capercaillie Tetrao urogallus, a forest grouse species known as sensitive to disturbance by human presence and infrastructure, was related to wind turbines and other environmental covariates in a wind farm in Sweden. During the lekking season, the probability of site‐selection by capercaillie decreased with increasing turbine noise, turbine visibility and turbine shadow. During summer, we found reduced resource selection with increasing proximity to the turbines (up to 865 m), turbine density, noise, shadow and visibility. Furthermore, we found an avoidance of turbine access roads. Due to the high collinearity of the wind turbine predictors it was not possible to identify the specific mechanism causing turbine avoidance. Our study reveals that forest dwelling species with known sensitivity to other forms of human disturbance (i.e. recreation) are also likely to be affected by wind turbine presence. In addition, we provide proximity thresholds below which effects are likely to be present as a basis for conservation planning.